ANALISIS PENGARUH SERVICE QUALITY, CUSTOMER PERCEIVED VALUE, DAN CORPORATE IMAGE TERHADAP CUSTOMER SATISFACTION SERTA DAMPAKNYA TERHADAP CUSTOMER LOYALTY (Studi Kasus pada Pelanggan Apotek Kimia Farma Pandanaran Kota Semarang) - Asri Hapsari, Devita; Yoestini, Yoestini (Diponegoro Journal of Management, 2020)
The increase of health problems and people’s need to have a better quality of life has triggered a big opportunity for companies to start entering the business of health service providers and products, one of which is a pharmacy. The rapid growth of the pharmacy business raises competition between companies that need to be anticipated. This study aims to determine and analyze the effect of service quality, customer perceived value, and corporate image on customer satisfaction and its impact on customer loyalty. The number of samples used were 160 respondents selected by purposive sampling technique through a questionnaire with Structural Equation Model (SEM) AMOS 24. The results showed that service quality, customer perceived value, and corporate image have a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty.